2021
DOI: 10.1017/s0007485321000687
|View full text |Cite
|
Sign up to set email alerts
|

Cascading effects of caffeine intake by primary consumers to the upper trophic level

Abstract: Secondary metabolites are central to understanding the evolution of plant–animal interactions. Direct effects on phytophagous animals are well-known, but how secondary consumers adjust their behavioural and physiological responses to the herbivore's diet remains more scarcely explored for some metabolites. Caffeine is a neuroactive compound that affects both the behaviour and physiology of several animal species, from humans to insects. It is an alkaloid present in nectar, leaves and even sap of numerous speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(82 reference statements)
0
1
2
Order By: Relevance
“…As a result, we hypothesize that S. manilae may exhibit higher physiological performance and locomotion ability by consuming a suitable dose of caffeine solution. However, most literature has shown that caffeine and other secondary metabolites might have some negative effects on parasitoids (Hall et al., 2021; Poyet et al., 2017; Thurston & Fox, 1972; Tougeron & Hance, 2021), with a few studies revealing that alkaloids might have no effects on parasitoids (Kostenko et al., 2013; Krauss et al., 2007; Urrutia et al., 2007), which is in contrast to our findings. The main reason for the difference is that previous papers concentrated on the tri‐trophic or multi‐trophic level (Tougeron & Hance, 2021).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As a result, we hypothesize that S. manilae may exhibit higher physiological performance and locomotion ability by consuming a suitable dose of caffeine solution. However, most literature has shown that caffeine and other secondary metabolites might have some negative effects on parasitoids (Hall et al., 2021; Poyet et al., 2017; Thurston & Fox, 1972; Tougeron & Hance, 2021), with a few studies revealing that alkaloids might have no effects on parasitoids (Kostenko et al., 2013; Krauss et al., 2007; Urrutia et al., 2007), which is in contrast to our findings. The main reason for the difference is that previous papers concentrated on the tri‐trophic or multi‐trophic level (Tougeron & Hance, 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…However, most literature has shown that caffeine and other secondary metabolites might have some negative effects on parasitoids (Hall et al., 2021; Poyet et al., 2017; Thurston & Fox, 1972; Tougeron & Hance, 2021), with a few studies revealing that alkaloids might have no effects on parasitoids (Kostenko et al., 2013; Krauss et al., 2007; Urrutia et al., 2007), which is in contrast to our findings. The main reason for the difference is that previous papers concentrated on the tri‐trophic or multi‐trophic level (Tougeron & Hance, 2021). For these trophic‐level studies, the experiments were tested on the parasitoids that parasitized the herbivores that fed on diets or plants containing alkaloids (Barker & Addison, 1996; Bultman et al., 2009, 2012; Campbell & Duffey, 1979).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation